Sources of production growth in Chinese agriculture:empirical evidence from penal data results 2001–2018. Issue 44 (20th September 2021) - Wang, Wei; Guo, Liwei
ABSTRACT: First of all, this article uses the regional panel data of Chinese agriculture ranging from 2001–2018 as samples, taking the relationship among the three, namely, factor allocation efficiency, biased technical progress and agricultural total factor productivity, as the entry point to systematically analyse the fluctuation of total factor productivity growth and its decomposition terms. Then, the bias index of technical progress and factor allocation are measured by relaxing the strict assumption of alternative elastic fixation and broadening the traditional hypothesis of neutral technical progress by using C-D functions, respectively. Finally, this article puts highlight on the following questions: What is the source of sustained growth of agricultural TFP at this stage? Which factor does the agricultural factor allocation efficiency depend on? Whether there are existing distortion and bias in agricultural factor allocation and if the bias of which is in step with agricultural-biased technical progress?